Mechanisms and impacts of anomalous high-salinity shelf water formation in the Ross Sea - X. Wang; X. Wang; Z. Zhang; Z. Zhang; Z. Zhang; Z. Zhang; C. Xie; X. Zhao; X. Zhao; C. Wang; C. Wang; C. Wang; et al. (The Cryosphere, 2025)
High-salinity shelf water (HSSW) acts as a precursor to the Antarctic Bottom Water and plays a critical role in regulating the global ocean circulation system. This study employs a high-resolution coupled ocean–sea ice–ice shelf model to analyze the interannual variation in HSSW formation in the Ross Sea, which is one of the major production sites of HSSW. We are particularly focused on anomalously high HSSW production during the winter of 2007. The results indicate that, in this winter, there were frequent passages of synoptic-scale cyclones that were centered near the front of the Ross Ice Shelf. The western flanks of these cyclones significantly enhanced offshore winds over the western Ross Ice Shelf Polynya, a major origin site of HSSW in the Ross Sea, leading to a sharp increase in ice production within this polynya. The HSSW formation resulting from brine rejection during ice freezing reached the highest volume of 16 000 km3 in 2007. However, the salinity and density of the Ross Sea during this period exhibited unexpectedly low values. This inconsistency was due to a rapid increase in ice shelf melting over the Amundsen Sea and Ross Sea during 2006–2007, with annual cumulative melt rates reaching a peak in recent decades. Meanwhile, the resulting large amount of meltwater was transported westward into the Ross Sea by notably strong slope and coastal currents in 2007, leading to large fluxes of freshwater flux into the Ross Sea. The interaction between enhanced HSSW formation driven by ice production and the large influx of meltwater highlights the complex dynamics that shape hydrographic variability in the Ross Sea.